Effect of Gd3+ ion distribution on structural and magnetic properties in nano-sized Mn–Zn ferrite particles. Issue 1 (January 2015) - Kumar, Ashok; Rana, Pawan S.; Yadav, M.S.; Pant, R.P.
Abstract: Nanoparticles of Gd 3+ ions doped Mn0.5 Zn0.5 Gd x Fe2− x O4 ( x =0.1, 0.2, 0.3, 0.4) mixed ferrite were prepared using chemical co-precipitation method. The X-ray diffraction measurements confirmed the formation of a cubic spinel structure. The structural parameters like crystallite size, lattice parameter and strain induced have been calculated. The lattice parameter increases with the increase in Gd 3+ ion concentration and shows non linear behaviour. HRTEM investigation confirms the nano size formation of the Gd doped Mn–Zn ferrite nanoparticles. EPR was used to evaluate resonance peak intensity, Lande's splitting factor ( g value), peak to peak line width (Δ H p – p ), spin concentration ( N s ) and relaxation time ( τ s ). Line width, line intensity, relaxation time and spin concentration increase with Gd 3+ ions doping (for x =0.1 to x =0.3) and then decrease for x =0.4, whereas the g value shows the reverse trend for the same composition. IR spectra shows two strong absorption bands at 570 cm −1 and 416 cm −1 of tetrahedral and octahedral bond stretching respectively in all the samples. IR spectrum also shows that Gd 3+ occupies the octahedral B-sites. Magnetic parameters such as saturation magnetization ( M s ), remanence ( M r ) and coercivity ( H c ) were measured by search coil method. The value of saturation magnetization increases from 29.94 emu/gm for x =0.1 to 46.01 emu/gm for x =0.4.